ANALYSIS OF COST OF SALES AND SALES ON NET INCOME - Muchamad Pahmi Ramdhani (Politeknik Negeri Bengkalis, 2021)
This study aims to analyze The cost of sales and sales of net income in retail trading companies listed on the Bursa Efek Indonesia. The population and sample in this study are the financial statements of 12 retail trading companies listed on the Bursa Efek Indonesia for the period 2016-2018. This research technique uses classic assumption test, multiple linear regression analysis, hypothesis test and determination coefficient test. The collection technique uses the documentation and literature review methods. And after the data was collected, the test analysis in this study was carried out with the help of IBM SPSS 26 for Windows. Based on the results of the F test that The cost of sales and sold together has a simultaneous effect on net income in 12 retail trading sub-sector trading companies listed on the Bursa Efek Indonesia.